The clothing quality consciousness of a selected group of male and female UP HRA students. - Tan, Ivy Benedicto; Ynchausti, Natividad S. (1991.)
The consumer behavior of quality consciousness in the selection of specific outwear items before purchase is studied with sex as a variable. Questionnaires were given to 48 female and 27 male junior and senior UP HRA students to determine the degree of quality consciousness of the subjects. The degree of importance the subjects placed on each aspect of clothing quality; namely, fit, workmanship, design, fabric and finishes used was also determined. It was found that both male and female subjects had an average degree of quality consciousness. Furthermore, there was NO SIGNIFICANT DIFFERENCE in the degree of quality consciousness of male and female students studied. While male and female subjects are both highly conscious of fit, and least conscious of workmanship, it was found that the male subjects gave more importance to fabric and finishes while the female respondents were more design conscious.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: UP HRA Students--Clothing.